Mitochondrial calcium transport during autophagy initiation - Sujyoti Chandra; Parul Katiyar; Aarooran S. Durairaj; Xinnan Wang (Mitochondrial Communications)
While it has been shown that Ca2+ dynamics at the ER membrane is essential for the initiation of certain types of autophagy such as starvation-induced autophagy, how mitochondrial Ca2+ transport changes during the first stage of autophagy is not systemically characterized. An investigation of mitochondrial Ca2+ dynamics during autophagy initiation may help us determine the relationship between autophagy and mitochondrial Ca2+ fluxes. Here we examine acute mitochondrial and ER calcium responses to a panel of autophagy inducers in different cell types. Mitochondrial Ca2+ transport and Ca2+ transients at the ER membrane are triggered by different autophagy inducers. The mitophagy-inducer-initiated mitochondrial Ca2+ uptake relies on mitochondrial calcium uniporter and may decelerate the following mitophagy. In neurons derived from a Parkinson's patient, mitophagy-inducer-triggered mitochondrial Ca2+ influx is faster, which may slow the ensuing mitophagy.